Find me the votes : a hard-charging Georgia prosecutor, a rogue president, and the plot to steal an American election - Isikoff, Michael; Klaidman, Daniel (Twelve, Hachette Book Group, 2024)
"In Find Me the Votes, two years of immersive reporting by Isikoff and Klaidman has produced the most authoritative and dramatic account yet of a defeated president's conspiracy to overturn the 2020 election and how a local Georgia prosecutor--a daughter of the civil rights movement--decided to indict him and his allies for his desperate attempt to hold on to power. From the beginning, Fani Willis saw Donald Trump's crimes as a voting rights case, and an attempt by the former president to deprive the citizens of Georgia of the franchise, a right for which her forebears had bled. Isikoff and Klaidman take us deep inside both the nerve center of Trump's effort to steal the election and the DA's team of prosecutors as they build their case against the president. Their reporting reveals new information on the plot to criminally seize voting equipment in several states; Sidney Powell's attempt to obtain preemptive pardons from Trump; and revelatory communications between the president and his co-conspirators. We see the prosecution take shape in Willis's office in the face of heinous threats of violent retaliation from Trump's supporters. With blockbuster original reporting and exclusive access to thousands of secret documents, emails, text messages, and audio recordings, Find Me the Votes is investigative journalism at its finest. The authors also conducted exclusive interviews with key sources in the Trump conspiracy, as well as with the president's top targets, including Georgia secretary of state Brad Raffensperger and the Fulton County DA's team-featuring hours of interviews with Fani Willis herself. This is riveting contemporary history, and a lasting account of the prosecution of a president who tested the rule of law as no president ever had before. Isikoff and Klaidman have written a story for the ages."--